20,000 leagues under the sea - Verne, Jules, 1828-1905 (Signet Classic, 2001)
Retells the adventures of a French professor and his two companions as they sail above and below the world's oceans as prisoners on the fabulous electric submarine of the deranged Captain Nemo.